Separation of albumin from bovine serum applying ionic-liquid-based aqueous biphasic systems - Rufino, Ana F. C. S. (2022)
In this work, the extraction and separation of bovine serum albumin (BSA) from its original matrix, i.e., bovine serum, was performed using a novel ionic-liquid-based aqueous biphasic system (IL-based ABS). To this end, imidazolium-, phosphonium-, and ammonium-based ILs, combined with the anions’ acetate, arginate and derived from Good Buffers, were synthesized, characterized, and applied in the development of ABS with K2HPO4/KH2PO4 buffer aqueous solutions at pH 7. Initial studies with commercial BSA revealed a preferential migration of the protein to the IL-rich phase, with extraction efficiencies of 100% obtained in a single-step. BSA recovery yields ranging between 64.0% and 84.9% were achieved, with the system comprising the IL tetrabutylammonium acetate leading to the maximum recovery yield. With this IL, BSA was directly extracted and separated from bovine serum using the respective ABS. Different serum dilutions were further investigated to improve the separation performance. Under the best identified conditions, BSA can be extracted from bovine serum with a recovery yield of 85.6% and a purity of 61.2%. Moreover, it is shown that the BSA secondary structure is maintained in the extraction process, i.e., after being extracted to the IL-rich phase. Overall, the new ABS herein proposed may be used as an alternative platform for the purification of BSA from serum samples and can be applied to other added-value proteins.